Efektivitas Nematoda Patogenik Serangga (Rhabditida: Steinernema dan Heterorhabditis) terhadap Penggerek Batang Padi Putih (Scirpophaga innotata) - Chaerani Chaerani; Bebet Nurbaeti (Jurnal Perlindungan Tanaman Indonesia, 2006)
White rice stem borer (Scirpophaga innotata) is a destructive insect pest which is difficult to control with various tactics. The possibility of the use of non-endemic natural enemies such as entomopathogenic nematodes (Rhabditida: Steinernema and Heterorhabditis) has been investigated in green house trials. Test of 12 isolates and species of Steinernema and Heterorhabditis originated from local and exotic sources revealed that H. indicus INA H4 was the most efficacious nematode by causing 74% larval and pupal mortality within rice stems. Reduction in plant damage due to nematode application could not be demonstrated as the experiment was limited to potted plants. Subsequent test using H. indicus INA H4 showed that increasing nematode concentration from 0.5 to 2.0x10^4 IJs/ml did not significantly affect insect mortality. The survival ability of H. indicus INA H4 infective juveniles on rice plant was less than 96 hours. Improvement of nematode application strategies including repeated spray, addition of antidesiccant, increasing spray volume and application at plant damage threshold or plant critical stage are therefore necessary to increase nematode effectiveness and simultaneously to reduce plant damage in field.